Snowbeast - Wallerstein, Herb, 1925-1985; Svenson, Bo, 1944-; Mimieux, Yvette; Douglas Cramer Productions; Cinetel Films ([Los Angeles, CA ] : Douglas Cramer Productions, 1977)
A Colorado ski resort is the center of a winter carnival celebration but something threatens to interrupt the festivities. Skiers have been found brutally slain out on the ski runs, torn apart by what appears to have been a wild animal. After eyewitnesses confirm what appears to be a large human-like creature leaving the scene of the latest attack, it becomes apparent to some that this is something more than a bear attack. While some people wish to warn the public and cancel the festival, there are others with a financial stake who wishes to continue the carnival no matter what the risk to the public.
Originally broadcast by NBC April 28, 1977.
Bo Svenson, Yvette Mimieux, Robert Logan, Clint Walker, Sylvia Sidney.
Cinematographer, Frank Stanley; editors, Carroll Sax, Dennis Mosher; music, Robert Prince.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Yeti -- Drama; Ski resorts -- Drama; Made-for-TV movies; Horror films; Feature films; Internet videos; Streaming video